2016 IEEE 35th International Performance Computing and Communications Conference (IPCCC) 2016
DOI: 10.1109/pccc.2016.7820663
|View full text |Cite
|
Sign up to set email alerts
|

Can maturity models support cyber security?

Abstract: We are living in a cyber space with an unprecedented rapid expansion of the space and its elements. All interactive information is processed and exchanged via this space. Clearly a well-built cyber security is vital to ensure the security of the cyber space. However the definitions and scopes of both cyber space and cyber security are still not well-defined and this makes it difficult to establish sound security models and mechanisms for protecting this space. Out of existing models, maturity models offer a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 10 publications
0
29
0
8
Order By: Relevance
“…To address these types of information and cybersecurity threats, a security framework is required to provide a common method to measure cybersecurity capabilities within an organisation (Le and Hoang, 2016). The metrics of such a framework should include a capability maturity model that incorporates not only the technical but also the social dimension of security (Carcary et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To address these types of information and cybersecurity threats, a security framework is required to provide a common method to measure cybersecurity capabilities within an organisation (Le and Hoang, 2016). The metrics of such a framework should include a capability maturity model that incorporates not only the technical but also the social dimension of security (Carcary et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Le and Hoang in [18] investigate existing cybersecurity maturity models to examine their strengths and weaknesses. They provide a comparison of 12 models mapped against five levels of maturity proposed by Humphrey (1989), concluding that models require relevant quantitative metrics for measurable and actionable assessment.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous paper [33], we compared twelve security maturity models in order to investigate their strengths and weaknesses. Cyber security maturity models have shown that they help managers to better manage security of their organizations [34] [35].…”
Section: Cyber Security Maturity Modelmentioning
confidence: 99%